Strategic planning, the real estate economy, and the production of new spaces of centrality. The case of Mexico City - Parnreiter, Christof (ERDKUNDE, 2015)
Taking Mexico City as a case study, this paper deals with the production of new economic centralities caused by global city formation. After sketching out the emergence of delimitable global city zones as the new downtown in Mexico City, the role the massive influx of foreign direct investment into the real estate economy and the growth of Mexico City’s producer service sector have played in the making of the new downtown is analysed. In the fourth section, I will argue that for the production of these new spaces of centrality urban policies and, in particular, planning mechanisms have been changed, in order to permit a faster, more flexible and site-specific handling of building projects. In that respect, strategic urban planning with its focus on key economic areas within the city and with its commitment to large urban projects has been critical. Finally, the paper shows that global circuits of knowledge and local pressures by the real estate economy have been the main mechanisms which have induced the changes in urban politics in Mexico City.